COMPARISON OF BRITISH AND AMERICAN ENGLISH - Ibayev Anvar Jurabekovich; Aktamova Dilnoza Bozorboy qizi; Zokirova Sevinch Quvonchbek qizi; Beknazarova Dinara Matlubjon qizi; Boliqulova Muxlisa Nomoz qizi; Ismatullayeva Bahora G’aybulla qizi (TADQIQOTLAR, 2026)
Abstract: This study compares British English and American English, two of the most widely used standardized forms of English. Even though they come from the same place in history, hundreds of years of being apart, developing their own cultures, and setting their own standards have caused big differences at different levels of language. The study investigates variations in pronunciation, lexicon, orthography, syntax, and pragmatic application. Special attention is paid to phonological features like rhotic and non-rhotic pronunciation, lexical differences between everyday and institutional language, orthographic differences caused by historical changes, and grammatical differences in how tense is used, how prepositions are used, and how collective nouns are used. The study also looks at the historical reasons why the two varieties diverged, such as the role of language planning and lexicography in the US and the preservation of traditional norms in Britain. Even though there are differences between British and American English, they are still understandable to each other and are used as main models in teaching English around the world. The results show that comparing these two types of language is important for understanding how languages change, improving communication between cultures, and helping people learn foreign languages more effectively.